Electronic-Word-of-Mouth dalam Live Streaming TikTok Shop Mendorong Impulse Buying di Kalangan Mahasiswa - cintya cintya; Hudi Santoso; Leonard Dharmawan (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study aims to analyze the influence of electronic Word of Mouth (e-WoM) in TikTok Shop Live Streaming on the impulse buying behavior of university students in Indonesia. The research employs a quantitative method with an associative approach and uses purposive sampling to gather data from 67 respondents, consisting of active university students who are TikTok users and have previously made purchases through TikTok Shop Live. The research instrument was developed based on the Information Adoption Model and the Online Impulse Buying Behavior Model. Data were analyzed using SPSS through a series of tests, including validity, reliability, normality, linearity, and simple linear regression analysis. The findings reveal that e-WoM has a positive and significant influence on impulse buying behavior, indicated by a correlation coefficient (R) of 0.531 and a significance value of < 0.001. The coefficient of determination (R²) of 0.282 indicates that e-WoM explains 28.2% of the variation in students’ impulse buying behavior, while the remaining 71.8% is influenced by other factors outside the research model. These results demonstrate that comments, testimonials, recommendations, and real-time interactions during live streaming can build trust and emotional engagement, thereby encouraging spontaneous purchasing decisions. This study provides empirical insights into the mechanism of e-WoM within the context of live streaming commerce and offers strategic implications for digital business practitioners in optimizing interactive communication to enhance consumer purchasing decisions.